2010
DOI: 10.1007/s11064-010-0234-z
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-1 Enhances Astrocytic BDNF Production and Improves Functional Outcome in Rats Following Ischemia

Abstract: Galectin-1, an endogenous mammalian lectin, has been implicated in a variety of CNS disorders. However, its role in cerebral ischemia is still elusive. In the present study, we investigated the effect of recombinant galectin-1 on production of astrocytic brain-derived neurotrophic factor (BDNF) and functional recovery following ischemia. Endogenous galectin-1 was found to be markedly upregulated, paralleled with increased astrocytic BDNF production under ischemic conditions both in vitro and in vivo. Administr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 38 publications
0
47
0
Order By: Relevance
“…Astrocytes are known to protect neurons from the insults of oxidative stress and excitotoxicity after brain ischemia (Rossi et al, 2007; Takano et al, 2009; Zhao and Rempe, 2010). Astrocytic brain-derived neurotrophic factor is known to reduce neuronal apoptosis in the ischemic boundary zone and improve functional recovery (Qu et al, 2010). Astrocytes are also known to play neuroprotective roles during brain ischemia by the expression of astrocyte-enriched miRNAs, including miR-181, miR-29 families, and miR-146a (Ouyang et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Astrocytes are known to protect neurons from the insults of oxidative stress and excitotoxicity after brain ischemia (Rossi et al, 2007; Takano et al, 2009; Zhao and Rempe, 2010). Astrocytic brain-derived neurotrophic factor is known to reduce neuronal apoptosis in the ischemic boundary zone and improve functional recovery (Qu et al, 2010). Astrocytes are also known to play neuroprotective roles during brain ischemia by the expression of astrocyte-enriched miRNAs, including miR-181, miR-29 families, and miR-146a (Ouyang et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that cultured astrocytes express and secrete Gal1 (Qu et al, 2010; Yin et al, 2012). Similarly, Gal1 is upregulated in GFAP+ cells in animal models of multiple sclerosis and cerebral ischemia (Qu et al, 2010; Stancic et al, 2011). Gal1-treated astrocytes show decreased proliferation and increased brain-derived neurotrophic factor (BDNF) secretion (Sasaki et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In models of focal brain ischemia and stroke, galectin-1 and -3 were found to be upregulated in astrocytes and microglial cells, respectively (35)(36)(37)(38).…”
Section: Ischemic Conditions Induce the Expression Of Galectin-3 As Wmentioning
confidence: 99%
“…Although the precise functions of galectins under ischemic conditions remain unclear, galectin-1 and -3 may improve the functional recovery of the damaged brain tissues (37,38). Galectin-1, -3, and -9 are strongly expressed in mesenchymal stem cells derived from bone marrow and umbilical cord blood (44)(45)(46)(47).…”
Section: Ischemic Conditions Induce the Expression Of Galectin-3 As Wmentioning
confidence: 99%